SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JURUSAN SEKOLAH MENENGAH KEJURUAN (SMKN 1 MASBAGIK) DENGAN METODE ROC DAN SAW - Zulkarnaen Zulkarnaen; Muhammad Azmi; Baiq Suci Nur Islamia; Yudi Sutaryana (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
Choosing a major at the vocational high school (SMK) level is a crucial decision that significantly influences students' educational and career paths. However, many students face difficulties in selecting a major that aligns with their interests and abilities. To support this process, this study designs a decision support system that integrates the Rank Order Centroid (ROC) and Simple Additive Weighting (SAW) methods. ROC is used to determine the weight of each criterion, while SAW is utilized to calculate the final score based on those weights. The system processes student data consisting of mathematics grades, science grades, English grades, and computer interest. The test results show that the system successfully recommends the most suitable major, with the highest score achieved in the TG (Technical Drawing) department for student A1. This system is expected to assist schools in assigning majors more objectively and accurately